Dietary Effects on Biological Parameters and Gut Microbiota of Harmonia axyridis - Huang, Zhendong; Zhu, Li; Lv, Jia; Pu, Zhanxu; Zhang, Lipin; Chen, Guoqing; Hu, Xiurong; Zhang, Zhenyu; Zhang, Hongyu (Frontiers in Microbiology, 2022)
The multicolored Asian lady beetle (Harmonia axyridis, H. axyridis, Coleoptera, Coccinellidae) is an effective biocontrol agent against agricultural pests. Previous studies have suggested that amount, type, and the quality of food can directly affect the biological aspects of H. axyridi. In this study, we investigated the influence of the food sources (Acyrthosiphon pisum Harris, Diaphorina citri Kuwayama, and artificial diets) on the gut microbiota diversity and the biology, reproductive variables, and population growth indicators of H. axyridis. Three kinds of diets were considered in this study: (1) HY: the adult of Acyrthosiphon pisum Harris (HY group); (2) HM: the adult of Diaphorina citri Kuwayama (HM group); (3) HR: artificial diets prepared by blending a portion of fresh homogenized pork liver (15g), honey (3g), distilled water (35ml) (HR group). We found that gut microbiota composition and diversity and the biological parameters differed when H. axyridi was fed with different diets. The abundance of Enterobacteriaceae was the highest in the HM group, followed by HY group, and was the lowest in the HR group. The abundance of Staphylococcaceae was highest in the HR group. Among the gut fungi, Davidiellaceae and Wallemiaceae were the highest and lowest in the HY group; Incertae_sedis were the major gut fungi in the HR group. Meanwhile, the changes of biological parameters may be correlated with the changes of Streptococcaceae abundance, Micrococcaceae abundance, Staphylococcaceae abundance, and Enterobacteriaceae abundance in responds to diet changes. To sum up, these data suggest that different diets can influence the changes in adult H. axyridis gut microbiota, consequently affecting the biological parameters.